Endometriosis Arising in a Cesarean Section Scar: A case report - Masereka, Robert; Kiyaka, Sonye Magugu; Sikakulya, Franck Katembo (International Journal of Surgery Case Reports, 2022)
Scar endometriosis is an uncommon variant of extra pelvic endometriosis, which develops at the scar site of previous abdominopelvic surgery and is seen in women during their reproductive period.
Keywords: Endometriosis; Cesarean; Abdominal wall scar